Nutrient Intake Associated with Anemia Status of Primary School Children - Riawan, Agus; Hardinsyah, Hardinsyah; Dewi, Mira (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aims to analyzse nutrient intake associated with the anemia status of primary school children in Bogor, Indonesia. A cross-sectional study was conducted on 500 children aged 8–14 years from 16 primary schools in Bogor, Indonesia. Anemia status was determined using hemoglobin level and analyzed using the cyanmethemoglobin method. Meanwhile, the dietary intake was assessed using 3x24 hours food recall. Anemia prevalance is 58.8%. Most of the subjects had indequate energy and nutrient intake. In this study, vitamin C adequacy level is the only nutrient associated with anemia status (p=0.03; OR=2.3; 95% CI:1.1–5.1).